Experiencias universitarias en estudiantes migrantes - Torcomian, Claudia Graciela (2017)
In this work the field of interest focuses on the experiences of college students who migrate to study the atmosphere to the city of Cordoba and its relationship to study processes in the course of Psychology. The purpose is to analyze the experiences of migrant students and their relationship with the processes of setting, autonomy and organization and identify the vital crises linked to migration during the race. The approach is qualitative and interpretative and constructive between the results found that migrate to study is an integral experience that combines the atmosphere of the city and the university. Migrate requires elaborate losses, overcome, generating autonomy, manage time and space in economic, social, emotional and academic.